A Review of the Current State of Off‐Label Therapies for Pediatric Inflammatory Bowel Disease - Yassin EL‐Najjar; Mary‐Joe Touma; Shuai Tan; Xiaoqin Zhou; Qi Liu (Pediatric Discovery)
ABSTRACT Off‐label use of biologic therapies in patients with pediatric inflammatory bowel disease (IBD) has seen an increase in utilization. In this paper, we review the current state of off‐label therapies in the pediatric IBD population. Real‐world use of ustekinumab (UST), vedolizumab (VDZ), upadacitinib (UPA), tofacitinib, and ozanimod in the adult population could prove positive outcomes in the pediatric population. Established off‐label therapies inch closer to comparable safety, efficacy, and outcomes in pediatric IBD use. Outcomes and use of newer biologic therapies in patients with pediatric IBD have improved with increased rates of steroid‐free clinical remission (SFCR). Novel therapies, including Janus kinase (JAK) inhibitors and sphingosine‐1‐phosphate receptor (S1Pr) modulators, require further studies but could also prove effective.